Fagofobia Como Síntoma Inicial de Demencia Frontotemporal: Reporte de Caso - Custodio, N (2022)
Introduction: Frontotemporal dementia is an important cause of dementia, and its diagnosis is complex due to the multiple neurocognitive manifestations that patients present. Eating disorders associated with this pathology have been reported, but phagophobia is an atypical manifestation. Case report: We present the case of a 74-year-old adult patient with onset of phagophobia associated with a progressive and significant loss of executive functions, compromised spatial orientation, presenting in parallel a marked compromise in instrumental daily activities, psychotic symptoms, apathy, gait disturbance and sleep problems. Conclusions: It is important that adult and older patients with eating disorders, particularly those who also present cognitive, behavioural and social dysfunction are evaluated to rule out the broad spectrum of frontotemporal dementia, since timely diagnosis and treatment can improve quality of life or slow its progression.